60th Anniversary of SID: Celebrating the Past and Looking Ahead. (18th July 2022) - Bhowmik, Achin
Abstract: SID has played a preeminent role in enabling the display technology ecosystem. The opportunity for SID to fuel the next wave of growth for imaging and display technologies is even more significant.